Perlawanan dan Pemulihan Identitas Perempuan dalam Media Lirik Lagu - Rizam, Masyithah Maghfirah; Darni, Darni (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2025)
Women often face patriarchal social constructions that influence their identity and roles in society. One significant cultural medium shaping the representation of women is song lyrics. This study explores how song lyrics serve as a medium to challenge patriarchal power and restore women's identities. Using critical discourse analysis grounded in Michel Foucault's theory, this research analyzes contemporary Madurese song lyrics reflecting themes of resistance and the reclamation of women's identities. The research method involves lyric analysis through a descriptive-analytical approach to identify resistance against patriarchal norms and the production of more independent and empowered female identities. Data were collected through documentation of relevant song lyrics, which were then analyzed using data reduction techniques and triangulation validation. The findings reveal that song lyrics not only represent the power structures that constrain women but also provide a space to voice freedom and resistance against gender stereotypes. Songs such as Kamalengan (Theft), Anyar Dedih Janda (Newly Divorced), and Selingkuh Tak Mareh (Affair Unresolved) depict women's experiences in facing stigma, inequality, and relational conflicts. These lyrics reflect a narrative resistance to exploitation and stigma while supporting identity recovery through resistance, empowerment, and self-control. Research on the impact of song lyrics on the critical awareness of listeners, particularly women, can provide further insights into the effectiveness of song lyrics as an empowerment tool. The findings of this study can serve as a basis for promoting the production of more inclusive works of art and as educational material to raise awareness of gender equality.